Increased Production of α-Linolenic Acid in Soybean Seeds by Overexpression of Lesquerella FAD3-1 - Yeom, Wan Woo; Kim, Hye Jeong; Lee, Kyeong-Ryeol; Cho, Hyun Suk; Kim, Jin-Young; Jung, Ho Won; Oh, Seon-Woo; Jun, Sang Eun; Kim, Hyun Uk; Chung, Young-Soo (Frontiers in Plant Science, 2020)
Soybean is a major crop that is used as a source of vegetable oil for human use. To develop transgenic soybean with high ɑ-linolenic acid (ALA; 18:3) content, the FAD3-1 gene isolated from lesquerella (Physaria fendleri) was used to construct vectors with two different seed-specific promoters, soybean β-conglycinin (Pβ-con) and kidney bean phaseolin (Pphas), and one constitutive cauliflower mosaic virus 35S promoter (P35S). The corresponding vectors were used for Agrobacterium-mediated transformation of imbibed mature half seeds. The transformation efficiency was approximately 2%, 1%, and 3% and 21, 7, and 17 transgenic plants were produced, respectively. T-DNA insertion and expression of the transgene were confirmed from most of the transgenic plants by polymerase chain reaction (PCR), quantitative real-time PCR (qPCR), reverse transcription PCR (RT-PCR), and Southern blot analysis. The fatty acid composition of soybean seeds was analyzed by gas chromatography. The 18:3 content in the transgenic generation T1 seeds was increased 7-fold in Pβ-con:PfFAD3-1, 4-fold in Pphas:PfFAD3-1, and 1.6-fold in P35S:PfFAD3-1 compared to the 18:3 content in soybean ‘Kwangankong.’ The increased content of 18:3 in the Pβ-con:PfFAD3-1 soybean (T1) resulted in a 52.6% increase in total fatty acids, with a larger decrease in 18:1 content than 18:2 content. The increase in 18:3 content was also maintained and reached 42% in the Pphas:PfFAD3-1 transgenic generation T2. Investigations of the agronomic traits of 12 Pβ-con:PfFAD3-1 transgenic lines (T1) revealed that plant height, number of branches, nodes, pods, total seeds and total seed weight were significantly higher in several transgenic lines than in non-transgenic soybean. Especially, an increase in seed size was observed upon expression of the PfFAD3-1 gene with the β-conglycinin promoter, and 6–14% higher seed lengths were measured from the transgenic lines.